Effect modification of greenness on PM2.5 associated all-cause mortality in a multidrug-resistant tuberculosis cohort. Issue 12 (7th December 2021) - Ge, Erjia; Gao, Jianhui; Wei, Xiaolin; Ren, Zhoupeng; Wei, Jing; Liu, Xin; Wang, Xiaomeng; Zhong, Jieming; Lu, Jingru; Tian, Xiaomei; Fei, Fangrong; Chen, Bin; et al.
Abstract : Rationale: Evidence for the association between fine particulate matter (PM2.5 ) and mortality among patients with tuberculosis (TB) is limited. Whether greenness protects air pollution-related mortality among patients with multidrug-resistant tuberculosis (MDR-TB) is completely unknown. Methods: 2305 patients reported in Zhejiang and Ningxia were followed up from MDR-TB diagnosis until death, loss to follow-up or end of the study (31 December 2019), with an average follow-up of 1724 days per patient. 16-day averages of contemporaneous Normalised Difference Vegetation Index (NDVI) in the 500 m buffer of patient's residence, annual average PM2.5 and estimated oxidant capacity Ox were assigned to patients regarding their geocoded home addresses. Cox proportional hazards regression models were used to estimate HRs per 10 μg/m 3 exposure to PM2.5 and all-cause mortality among the cohort and individuals across the three tertiles, adjusting for potential covariates. Results: HRs of 1.702 (95% CI 1.680 to 1.725) and 1.169 (1.162 to 1.175) were observed for PM2.5 associated with mortality for the full cohort and individuals with the greatest tertile of NDVI. Exposures to PM2.5 were stronger in association with mortality for younger patients (HR 2.434 (2.432 to 2.435)), female (2.209 (1.874 to 2.845)), patients in rural (1.780 (1.731 to 1.829)) and from Ningxia (1.221 (1.078 to 1.385)). Cumulative exposures increased the HRs of PM2.5 -related mortality, while greater greenness flattened the risk with HRs reduced in 0.188–0.194 on average. Conclusions: Individuals with MDR-TB could benefit from greenness by having attenuated associations between PM2.5 and mortality. Improving greener space and air quality may contribute to lower the risk of mortality from TB/MDR-TB and other diseases.